Estrutura genética da população brasileira estimada a partir de microssatélites de uso forense - Laélia Maria Pinto (2010)
Brazil has an admixture population constitute of the mixed ethnicity. The population structure knowledge may help in forensic genetics analyses that used microsatellites markers. The samples are from Biocod Biotecnologia database, this data was constructed the results of paternity tests collect in the whole country. The aim was microsatellites markers describe and study of population structure. In this analyses 18 markers are choice and divided into two sets: D10S1237, D12S391, D13S317, D16S539, D16S753, D21S1437, D22S534, D22S689, D2S1338, D3S1358, D3S2387, D3S2406, D5S818, D5S2503, D7S820, D9S938, SE33 e TH01. The brazilian population was divided according to brazilian states. The forensic statistical analyses, power of discrimination (PD), matching probability (PM), PIC, power of exclusion (PE) and mutation rates, showed significant results whom is closed to the CODIS system results, as the brazilian studies as the world studies. These microsatellites appear as great tools for forensic analyses so its results are compatible with the FBI markers. Together, the two sets showed PD=0,933, PE=0,573, an average mutation rate = 10-3 and typical paternity index with 99,9999% paternity probability. The best marker was SE33 that is the most informative in agree with others studies what this marker was included. The AMOVA is based in the Wright (1951) F’statistics and was use for population structure analyses, in this analyses the variation is bigger into population than among populations, the Fst values to point to non-structure population, the Fis results and Hardy-Weinberg deviations indicated a deficiency of heterozygotes what can be explain for Wahlund’s principle. The inclusion of more microsatellites markers in this kind of study may show best results for the population structure analyses, at the same time this markers are very applicable for forensic studies, and population structure studies are useful for forensic analyses that are totally dependent of knowledge about markers and population involved in this cases.